2016
DOI: 10.1007/s12017-016-8438-2
|View full text |Cite
|
Sign up to set email alerts
|

Pro198Leu Polymorphism in the Glutathione Peroxidase 1 Gene Contributes to Diabetic Peripheral Neuropathy in Type 2 Diabetes Patients

Abstract: Glutathione peroxidase 1 (Gpx1) is an endogenous antioxidant enzyme. The T allele of the Pro198Leu polymorphism in the Gpx1 (rs1050450, 198C > T) gene is associated with reduced enzyme activity. The aim of this study was to evaluate the association between Pro198Leu polymorphism and risk of diabetic peripheral neuropathy (DPN). We examined 1244 T2DM patients and 730 healthy controls. In the patient group, 33 % had diabetic peripheral neuropathy. All subjects were genotyped for the Gpx1 Pro198Leu polymorphism b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
(48 reference statements)
2
16
0
Order By: Relevance
“…Some studies [62,63] underline the importance of maintaining an appropriate expression and activity of this selenoperoxidase to control redox balance and glucose and lipid metabolism. GPX1 polymorphism with risk of diabetes and obesity in different populations [64][65][66][67][68]. Oxidative stress-induced intestinal injury has been reduced by the addition of SOD, glutathione peroxidase, and N-acetylcysteine, which reduces intestinal tissue tumor necrosis factor-a concentrations with anti-inflammatory and antioxidant properties [69,70].…”
Section: Glutathione Peroxidasementioning
confidence: 99%
“…Some studies [62,63] underline the importance of maintaining an appropriate expression and activity of this selenoperoxidase to control redox balance and glucose and lipid metabolism. GPX1 polymorphism with risk of diabetes and obesity in different populations [64][65][66][67][68]. Oxidative stress-induced intestinal injury has been reduced by the addition of SOD, glutathione peroxidase, and N-acetylcysteine, which reduces intestinal tissue tumor necrosis factor-a concentrations with anti-inflammatory and antioxidant properties [69,70].…”
Section: Glutathione Peroxidasementioning
confidence: 99%
“…These results appeared to suggest that lower expression of Nrf2 would lead to reduced antioxidative function. This is particularly important from a DM perspective whereby ROS can be generated from the auto oxidation of glucose, activation of protein kinase C, methylglyoxal formation and glycosylation, hexosamine metabolism and the formation of sorbitol (Buraczynska et al 2017). A previous study has revealed that ROS accumulation is induced by Nrf2 inhibition (Yang et al 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…ROS are targeted for removal by antioxidants and enzymes such as superoxide dismutases (SOD), catalase, glutathione peroxidases (GPx), peroxiredoxins, and thioredoxins. In preclinical diabetic rodent models and in diabetic patients, the expression of antioxidants such as GPx has been shown to be reduced resulting in increased markers of oxidative damage 14, 15, 16…”
Section: Reactive Oxygen Species and Oxidative Stressmentioning
confidence: 99%